Data protection in the personal data processing - Філоненко, Сергій Федорович; Швець, Валеріан Анатолійович; Мужик, Ігор Мирославович (Ukrainian Information Security Research Journal, 2013)
Processing of personal data, which is obligatory for any institution or organization, requires implementation of personal data processing information systems and definitely their security. The majority of existing information security methods and techniques is focused on the security of corporate information systems resources. Such techniques do not always take into account the special requirements for data processing. This fully applies to the processing of personal data protection, the security of which is provided by the current legislation. Approaches to the protection of personal data processed in automated information systems were discussed. The classification of threats to personal data that may occur when processing them in automated systems was brought. We considered the aims and methods of minimizing such threats including comprehensive measures to protect personal data. The ways and means of personal protection methods of personal data were considered. The priorities of forming the overall personal data protection system were defined.